2019
DOI: 10.1182/blood-2019-126822
|View full text |Cite
|
Sign up to set email alerts
|

Serum Albumin Level, but Not Nutritional Risk Index Predicts Outcomes in Acute Leukemia Patients after Allo-HSCT

Abstract: Background: Nutritional problem is a key aspect of all severe diseases that always "keep in the shadows". There are different factors, such as intensive chemotherapy, constant nausea, severe infections, time for donor search that affect nutritional status in leukemia patients who underwent allogeneic stem cell transplantation (allo-HSCT). This study aimed to evaluate the impact of different "nutritional status assessment tools" on outcomes of allogeneic hematopoietic cell transplantation. Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…There are a variety of factors that affect the nutritional condition of patients undergoing allogeneic HSCT, including intense chemotherapy, persistent nausea, severe infections, and the donor search time. Additionally, numerous studies have indicated that the pre-operative nutritional status, including albumin levels ( 11 , 12 ), weight loss ( 13 ), and low body mass index (BMI), is related to poor clinical prognosis for patients following HSCT. Chee et al.…”
Section: Introductionmentioning
confidence: 99%
“…There are a variety of factors that affect the nutritional condition of patients undergoing allogeneic HSCT, including intense chemotherapy, persistent nausea, severe infections, and the donor search time. Additionally, numerous studies have indicated that the pre-operative nutritional status, including albumin levels ( 11 , 12 ), weight loss ( 13 ), and low body mass index (BMI), is related to poor clinical prognosis for patients following HSCT. Chee et al.…”
Section: Introductionmentioning
confidence: 99%